Development, validity and effects of paraplegia fitness integrated training (PARAFIT) program to increase physical activity and fitness in individuals with spinal cord injury / Noor Hafifi Noor Hisham - Noor Hisham, Noor Hafifi (2022)
Individuals with spinal cord injury (SCI) have low levels of physical activity (PA), exercise self-efficacy (ESE), physical fitness, and adherence to exercise. Secondary complications such as cardiovascular disease, diabetes, and obesity may occurred as a result of these factors. Therefore, there is a need to develop a program to enhance active lifestyle after SCI. This study aims to develop an exercise program and education tool called Paraplegia Fitness Integrated Training (PARAFiT) and examine its effects on the level of PA, ESE, physical fitness, and adherence to exercise. The development consisted of phase I (validity of the study) and phase II (the experimental study). The non-randomized controlled trial study was designed for wheelchair-bound SCI individuals whereby the participants (n=44) were non-randomly assigned to either an intervention group (PARAFiT combined with conventional physiotherapy) or control group (conventional physiotherapy alone) with 22 participants in each group. Participants in the PARAFiT group (n=19) and control group (n=20) completed their involvements in the 16-week experiment. The Physical Activity Scale for Individuals with Physical Disabilities (PASIPD) and the Exercise Self-Efficacy Scale (ESES) were utilized to measure the level of PA and ESE respectively at baseline, 8th week, 12th week, and 16th week. The physical fitness outcome for cardiorespiratory fitness, shoulder strength and hand grip strength utilized the 6 Minute Push Test (6-MPT), BIODEX isokinetic machine, and JAMAR® handheld dynamometer respectively at the 4 th week and 8 th week. The exercise adherence was monitored throughout the program using an exercise diary. In phase I, the development shows that the program was consisted of five topics such as (1) The types of PA and exercise (2) The benefits of PA and exercise (3) Coping strategies (4) Formulation of goal settings (5) The risk and safety. The content experts also stated the education material was 75% valid to be able to increase the PA level after SCI. The pilot study was shown that the PARAFiT program was safe and highly adhered by the consumers. In phase II, the results of the 2-way repeated measure mix ANOVA showed no significant differences in PA (p = 0.356) but significant in ESE (p = 0.001) levels between the intervention and control groups from baseline to week 16th .